2022
DOI: 10.1021/acsaem.2c02392
|View full text |Cite
|
Sign up to set email alerts
|

Full-Area Passivating Hole Contact in Silicon Solar Cells Enabled by a TiOx/Metal Bilayer

Abstract: Passivating contacts, featuring dual functions of defect passivation at the semiconductor surface and extracting one type of charge carrier, are recognized as the key enabler in achieving high-efficiency Si solar cells. In particular, a dopant-free and full-area passivating hole contact is critical to replace the conventional rear structure that features a partial Si-metal contact design with insulator interlayers. Herein, titanium oxide (TiO x ) nanolayers (∼5 nm) grown by atomic layer deposition over the ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The surface passivation is degraded with a 4.2 eV work function contact (Al) before improving again with a further decrease in the contact work function. Matsui et al [20] also reported a significant degradation of the surface passivation when using Al contacts for devices with p-type Si wafers, which is in good agreement with our results.…”
Section: Impact Of the Contact Work Functionsupporting
confidence: 92%
See 3 more Smart Citations
“…The surface passivation is degraded with a 4.2 eV work function contact (Al) before improving again with a further decrease in the contact work function. Matsui et al [20] also reported a significant degradation of the surface passivation when using Al contacts for devices with p-type Si wafers, which is in good agreement with our results.…”
Section: Impact Of the Contact Work Functionsupporting
confidence: 92%
“…Significant degradation of the surface passivation was noticed when an Al layer was used for p ‐type devices. [ 20 ] These results indicate that the contact work function influences the surface recombination statistics despite the interlayer between the contact and the Si. However, no direct evidence, such as a variation of the surface saturation current density ( J 0s ) before and after metallization, has been presented, mainly since common lifetime measurement techniques have severe limitations when applied to metallized samples.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Finally, while in this work we have focused on applications as an electron selective contact, it is worth noting that TiO x has also been demonstrated as an efficient hole-selective passivating contact in c-Si solar cells. 23,24,47 This manipulation of TiO x to operate as an efficient hole-selective contact would potentially allow the fabrication of novel architectures of c-Si solar cells, using TiO x /TCO stacks on both sides of Si to form heterojunction devices. However, in order to induce the TiO x /TCO stack to serve as efficient hole-selective contacts without signicant electrical losses (ll factor issues), the TCO material must have a high work function with high mobility and low sheet resistance.…”
Section: Other Concerns and Possible Solutionsmentioning
confidence: 99%